SOSIALISASI BAHAYA NARKOTIKA SEBAGAI UPAYA PENCEGAHAN PENYALAHGUNAAN NARKOTIKA DI KALANGAN MAHASISWA - Muthia Aryuni; Yuli Fitriana; Muhammad Ardi Munir; Gabriella Bamba Ratih Lintin (LP2M Universitas Hasanuddin, 2023)
Based on the results of a survey by the National Narcotics Agency of the Republic of Indonesia and LIPI in 2019, the province of Central Sulawesi is one of the largest contributors to drug abuse and ranks fourth in Indonesia (Rafii, 2020a). Adolescence and early adulthood are a period of searching for identity and acknowledging the truth. The desire to seek satisfaction and fulfillment of the vulnerable ego makes them face various problems. This can have a negative impact if the environment does not get attention from adults because it can lead to negative things such as free sex, and drug abuse. This community service activity aims to provide knowledge about the dangers of narcotics to students using the socialization method. The target of this activity was student representatives from the Student Executive Board (BEM) of each faculty at Tadulako University (UNTAD) Palu, with a total of 30 socialization participants. The activities were carried out using the lecture and discussion method for two days in the new Hall of the UNTAD Faculty of Medicine. Result: there is an increase in the average value (mean) of 81.90 and the NGain score of 77% which is included in the effective category in increasing knowledge about the dangers of narcotics in students before and after being given socialization. — Berdasarkan hasil survey BNN RI dan LIPI pada tahun 2019 lalu, provinsi Sulawesi Tengah menjadi salah satu daerah penyumbang terbesar penyalahgunaan narkoba dan berada pada urutan keempat se-Indonesia (Rafii, 2020a). Masa remaja dan dewasa awal pada dasarnya merupakan masa pencarian jati diri serta pengakuan akan kebenaran. Keinginan mencari kepuasan dan pemenuhan ego rentan membuat mereka dihadapi dengan berbagai permasalahan. Hal ini dapat berdampak negatif bila lingkungan tersebut tidak mendapakan perhatian dari orang dewasa karena dapat menjurus kearah yang negatif seperti seks bebas, penyalahgunaan narkotika. Kegiatan pengabdian masyarakat ini bertujuan untuk memberikan pengetahuan tentang bahaya narkotika kepada mahasiswa dengan metode sosialisasi. Sasaran kegiatan ini adalah perwakilan mahasiswa pengurus Badan Eksekutif Mahasiswa (BEM) setiap fakultas di Universitas Tadulako (UNTAD) Palu, dengan jumlah total peserta sosialisasi sebanyak 30 orang. Pelaksanaan kegiatan dilakukan dengan metode ceramah dan diskusi selama dua hari di Aula baru Fakultas Kedokteran UNTAD. Hasil: terdapat peningkatan nilai rata-rata (mean) sebesar 81,90 dan NGain score sebesar 77% yang termasuk dalam kategori efektif dalam meningkatkan pengetahuan tentang bahaya narkotika pada mahasiswa sebelum dan setelah diberikan sosialiasasi.